Vegetative Growth Responses to Applications of Compost from Biomass of the Same and Different Crop Species and in Vitro Test of Self-DNA Effects - Sari, Retno Purnama; Santosa, Dwi Andreas; Sudadi, Untung (Food, Agriculture and Natural Resources - NETWORKS, 2025)
Returning-back unharvested crop biomass into soil which is intended to maintain soil fertility status is now facing a challenge concerning self-DNA negative impacts related to the application of compost prepared from biomass of the same crop species at certain compost maturity stage. This study aimed at to evaluate the application effects of composts prepared from biomass of the same and different food crop species with different composting periods on the vegetative growth of rice, maize, and string beans and of DNA extracts from the applied composts on seed germination of the studied crops. The experiment applied CRD with 10 treatments [control, k (compost materials): rice (P), maize (J), and string beans (K) biomass, and composting periods: 0, 30, and 90 d]. DNA was isolated by the modified CTAB method. The results showed that application of mature compost supported the vegetative growth of the test crops, while kP30 and kJ30 treatments, stands respectively for the application of 30 days-composted rice and maize biomass, showed inhibitory effect to the vegetative growth of the same species (rice or maize compost applied to rice or maize cropping). However, in vitro self-DNA inhibition effect was inconsistent and therefore considered not occurred in this experiment.